The Role of the Islamic Personal Development Program in Instilling Islamic Character Values in Students at SMPS IT Al-Hijrah - Fitrianingrum Br. Pane; Hadis Purba; Muhammad Basri (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2024)
This research is motivated by the decline in adolescent morals which leads to the inability to reflect a good Muslim and the many competency standards that students must have, especially in integrated Islamic schools. The aim of this research is to determine the role of Islamic Personal Development (BPI) in planning, implementing and maintaining the instillation of Islamic character values in students. This type of research is qualitative with a phenomenological approach. Data collection from observations, interviews and documentation studies. Data analysis techniques are data reduction, data presentation, and drawing conclusions. To ensure the validity of the data, source triangulation techniques were used. The research results show that BPI has a role in planning the cultivation of Islamic character values through preparing a master plan for other program activities. BPI has a role in instilling Islamic character values through activities in the main program and supporting programs. BPI has a role in maintaining the cultivation of Islamic character values through filling out mutabaah yaumiyah and BPI Report Cards.